CODE-SWITCHING AMONG BILINGUAL ENGLISH SPEAKERS - Murayeva Patilabonu Sherali qizi,; Ruzmetova Diana Kamilovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT This essay explores the phenomenon of code-switching among English bilingual speakers, focusing on the reasons and methods by which individuals shift between languages  during  conversations.  Code-switching  occurs  when  bilingual  speakers transition from one language to another within a single dialogue or even within a single sentence. This paper reviews the social, psychological, and contextual bases for code-switching and what role it plays in communication. Through reading earlier studies and literature, this paper asserts that code-switching is not any longer a sign of language deficiency as previously thought, but rather more intricate communication strategies whereby bilingual speakers communicate their identity and negotiate social situations. The research validates that code-switching is essential bilingual communication and it must receive more acknowledgment in language instruction and policy.